2009
DOI: 10.3174/ajnr.a1472
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Constructive Interference in Steady State Sequence Alone for Follow-Up Imaging of Vestibular Schwannomas

Abstract: BACKGROUND AND PURPOSE: Vestibular schwannoma (VS) is a benign, slow-growing tumor, and radiologic monitoring is an acceptable alternative to surgery in small lesions and in elderly patients. MR imaging with contrast is the study of choice in the follow-up of these lesions. However, gadoliniumbased contrast agents have side effects and should be used only when definitely indicated. The purpose of this study was to evaluate the diagnostic accuracy of the constructive interference in steady state (CISS) sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…They reported moderate interobserver agreement in evaluating progression with the CISS sequence; however, our study shows excellent interobserver agreement in evaluating progression using the CISS sequence. In our opinion, the differing degrees of interobserver agreement reported in the two studies are due to different measurement methods; we evaluated tumor growth using annual growth rate measurements in contrast to the qualitative measurements that were used in the Ozgen study (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported moderate interobserver agreement in evaluating progression with the CISS sequence; however, our study shows excellent interobserver agreement in evaluating progression using the CISS sequence. In our opinion, the differing degrees of interobserver agreement reported in the two studies are due to different measurement methods; we evaluated tumor growth using annual growth rate measurements in contrast to the qualitative measurements that were used in the Ozgen study (7).…”
Section: Discussionmentioning
confidence: 99%
“…There is only one report in the literature regarding the diagnostic accuracy of the CISS sequence in the follow up of vestibular schwannomas. Ozgen et al (7) reported that the CISS-only MRI technique may be an alternative to routine contrast-enhanced MRI in following up lesion size in patients with vestibular schwannomas. They reported moderate interobserver agreement in evaluating progression with the CISS sequence; however, our study shows excellent interobserver agreement in evaluating progression using the CISS sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular schwannomas (VSs) are benign tumors that arise from the Schwann cells of the vestibulocochlear nerve sheaths . VSs are typically slow‐growing tumors with an average growth rate of 1.2 mm per year and estimates of growth ranging from 30% to 90% .…”
Section: Introductionmentioning
confidence: 99%
“…Constructive interference in steady state (CISS) is a T2‐weighted MRI imaging modality that has been suggested as a diagnostic and surveillance imaging alternative to GdT1 MRI. CISS imaging is commonly obtained prior to contrast administration and provides high‐spatial resolution, which allows for good contrast between cerebrospinal fluid and neighboring structures . Previous studies have shown comparable sensitivity and specificity of CISS in comparison to GdT1 MRI without the risks of side effects due to contrast infusion .…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional constructive interference in steady-state (CISS) MR imaging is a slow version of fully refocused steady-state sequences (Chavhan et al 2008) and provides a high spatial resolution image with clear contrast between fluid and other structures, and is reported to have high sensitivity for detecting IAC lesions and cerebellopontine angle (CPA) lesions without additional contrast agents (Casselman et al 1993;Curtin 1997). Therefore, the CISS sequence is frequently used for the diagnosis and follow up of IAC and CPA lesions combined with T1-weighted MR imaging with Gd, and several reports have recently suggested that only CISS imaging may be suitable for the regu-lar follow up of vestibular schwannomas (Ozgen et al 2009;Bayraktaroglu et al 2011). However, no reports discuss the availability and limitations of the CISS sequence for diagnosing IAC osteomas.…”
Section: Introductionmentioning
confidence: 99%